Simethicone Medication Should Be Avoided in Infants Receiving Oral Lactase Treatment - Ekin Say Yildirim; Adem Aydin; Tolga Ince; Zeynep Varol; Belgin Ünal; And Demir (MDPI AG, 2024)
Objective: In this retrospective study, we assessed the efficacy of oral lactase in infants with lactose intolerance in terms of sex, birth weight, and interference by other medications. Methods: The study was conducted on patients aged 0-6 months who had been diagnosed with lactose intolerance on admission to the Department of Social Pediatrics at Dokuz Eylul University. Demographic data, the onset of symptoms, and medications used were recorded. Results: We found that 86.7% of the infants responded to lactase, with no significant differences based on sex, birth weight, or age at symptom presentation. We observed, however, that the efficacy of treatment did improve over time, thereby deriving benefits from intestinal development and adaptation. Interestingly, the response to lactase was reduced in infants receiving concomitant simethicone for colic symptoms, suggesting a potential drug interaction, while probiotics had no impact on treatment outcomes. Conclusions: We advise against using additional medications with oral lactase, pointing out a possible interaction with simethicone that might decrease the effectiveness of treatment.